2023
DOI: 10.3390/diagnostics13132299
|View full text |Cite
|
Sign up to set email alerts
|

Super Formula for Diagnosing Disseminated Intravascular Coagulation Using Soluble C-Type Lectin-like Receptor 2

Abstract: The scoring systems for disseminated intravascular coagulation (DIC) criteria require several adequate cutoff values, vary, and are complicated. Accordingly, a simpler and quicker diagnostic method for DIC is needed. Under such circumstances, soluble C-type lectin-like receptor 2 (sCLEC-2) received attention as a biomarker for platelet activation. Materials and Methods: The diagnostic usefulness of sCLEC-2 and several formulas, including sCLEC-2xD-dimer, sCLEC-2/platelet count (sCLEC-2/PLT), and sCLEC-2/PLT × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 45 publications
0
12
2
Order By: Relevance
“…I read with great interest the article by Akitaka Yamamoto et al that was recently published in Diagnostics [ 1 ]. I congratulate the authors for their work, which contributes to the early diagnosis of disseminated intravascular coagulation (DIC) or pre-DIC using soluble C-type lectin-like receptor 2 (sCLEC-2), a novel platelet activation biomarker.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…I read with great interest the article by Akitaka Yamamoto et al that was recently published in Diagnostics [ 1 ]. I congratulate the authors for their work, which contributes to the early diagnosis of disseminated intravascular coagulation (DIC) or pre-DIC using soluble C-type lectin-like receptor 2 (sCLEC-2), a novel platelet activation biomarker.…”
mentioning
confidence: 99%
“…My research group also previously reported the clinical utility of sCLEC-2 measurement for the diagnosis of sepsis-induced DIC (SID) [ 2 ]. I would like to offer the following remarks on the report by Yamamoto et al [ 1 ] regarding the relationship between sCLEC-2 concentrations and patients with DIC.…”
mentioning
confidence: 99%
“… 25 The super formula of the sCLEC-2 × D-dimer/platelet count also increases the diagnostic ability of DIC and pre-DIC. 31 These findings suggest that the super formula of the sCLEC-2 × D-dimer can diagnose both platelet activation and hypercoagulability. Several formulae have been developed for diagnosing thrombosis; the sCLEC-2 × D-dimer formula may indicate the activation of coagulation, platelets, and fibrinolysis; the sCLEC-2/PLT ratio may indicate platelet activation and consumption but does not indicate coagulation and fibrinolysis; the sCLEC-2 × D-dimer/PLT formula includes the activation of coagulation, platelets, and fibrinolysis with the consumption of clotting factors 48 , 49 ; and the sCLEC-2/D-dimer ratio may be useful for making the differential diagnosis between arterial and venous thrombosis.…”
Section: Discussionmentioning
confidence: 85%
“… 46 Although the sCLEC-2/PLT ratio was useful in patients with thrombocytopenia, this ratio was not superior to sCLEC-2 alone in this study without thrombocytopenia. Similarly, the sCLEC-2 × D-dimer/PLT formula was useful for diagnosing DIC 31 ; however, this formula was not more useful than the sCLEC-2 × D-dimer formula in patients without thrombocytopenia.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation